Clinical Value and Potential Mechanisms of Oxysterol-Binding Protein Like 3 (OSBPL3) in Human Tumors - Hao, Na; Zhou, Yudong; Li, Yijun; Zhang, Huimin; Wang, Bin; Liu, Xiaona; Ren, Yu; He, Jianjun; Zhou, Can; Tang, Xiaojiang (Frontiers in Molecular Biosciences, 2021)
Cancer remains one of the major culprits causing disease-related deaths. A lack of broad-spectrum and effective multi-cancer therapeutic targets have limited the prolongation of cancer patients' survival. Therefore, it is important to explore novel oncogenic genes or versatile targets and perform a comprehensive analysis to assess its roles in the process of tumorigenesis. OSBPL3 protein is an intracellular lipid receptor of the oxysterol-binding protein superfamily, which participates in some pathological and physiological processes in tumor progression, however, its clinical roles and potential mechanisms in cancers remains unknown. Thus, we aimed to systematic explore the potential oncogenic roles of OSBPL3 across thirty-three tumors mainly using multiple web-based, publicly-available tools, including the cancer genome atlas and Gene expression omnibus, Genotype Tissue-Expression, cBioPortal, and Human Protein Atlas database. OSBPL3 is highly expressed in major subtypes of cancers, which distinctly associated with prognosis of tumor patients. We observed X676_splice/V676G alteration in the oxysterol domain and frequent mutations of OSBPL3 involves the cell survival in skin cutaneous melanoma. We also first presented that the expression of OSBPL3 was associated with tumor mutational burden (TMB) in nine cancer types. Additionally, OSBPL3 shown an enhanced phosphorylation level S426, S251 and S273 locus within the pleckstrin homology domain in several tumors, such as breast cancer or lung adenocarcinoma. And OSBPL3 expression was associated with active immune cells (CD8+ T cell) and cancer-associated fibroblasts in breast cancer, colon adenocarcinoma and kidney renal clear cell carcinoma and immune checkpoint genes in more than 30 tumors, but weekly association with immune suppress cell (Myeloid-derived suppressor cells, T regulatory cells). Moreover, protein processing and mRNA metabolic associated functions were involved in the functional mechanisms of OSBPL3. Our study first demonstrated a novel agent OSBPL3 plays an important role in tumorigenesis from the perspective of publicly databases and clinical tumor samples in various cancers, which provide comprehensively insights of its biological functions and may be helpful for further investigation.